Legal Consequences on Cooperative Management Who Neglect to Carry Out Their Functions Resulting in Loss of Cooperatives Based on the 1992 Cooperative Law - Mariyadi Mariyadi; Muhammad Arifin; Alpi Sahari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Cooperatives are managed with the aim of improving the welfare of its members and society as a whole. As a legal entity, cooperatives have the authority and ability to carry out every legal relationship, both externally and internally, with humans or other business entities. Cooperatives as legal entities are represented by their organs, which in this case are cooperative management, supervisors and member meetings. There are many cases of cooperatives disbanding due to the negligence of the management which resulted in cooperative losses. Based on the results of the study it was found that the position of the cooperative management in Law Number 17 of 2012 concerning Cooperatives in Article 29 stipulates that the Cooperative Management is a representative of a legal entity, in this case cooperatives. That the legal consequences for cooperative management who neglect to carry out their functions resulting in cooperative losses based on the 1992 Cooperative Law depend on the accountability of the management at the Membership Meeting. If the report is accepted, then there will be no legal consequences. That the responsibility of the cooperative management who is negligent in carrying out its functions so as to result in the loss of the cooperative can be burdened with personal responsibility because the management as the party entrusted with the task of managing the cooperative can be burdened if it can be proven that the management has committed an unlawful act as stipulated in Article 1365 of the Civil Code.